Teori Mekanisme Pasar Menurut Ibnu Khaldun - Angg Rinjani, Heru (RJABM (Research Journal of Accounting and Business Management), 2024)
Ibn Khaldun's full name is Abdurrahman Zaid Waliuddin bin Khaldun, born in Tunisa on 1 Ramadan 732 H, coinciding with May 27, 1332 AD. Ibn Khaldun is the most prominent Muslim intellectual figure and most of his thoughts in various fields, such as economics, politics, sociology and culture. (1332-1406). Ibn Khaldun studied some of the problems and phenomena of life about society, history and the economy that had never been studied by scientists before. He explained all economic problems and connected them with verses in the Qur'an. This is proof that various economic activities have been regulated in Islam. In addition, his writings and works show that Ibn Khaldun is the father and economist who preceded Adam Smith, Ricardo and European economists.